Meteorological observations of quasi-stationary long-lived convective boundary layers ... - Kadantsev, Evgeny; Repina, Iryna (https://b2share.eudat.eu, 2020)
Experimental data for validation of the non-conventional vision on convective turbulence proposed by Zilitinkevich et al., 2020: https://arxiv.org/abs/2005.07680. The data were obtained from meteorological observations at the North-East Siberian station Tiksi in the conditions of long-lived convective boundary layer typical of arctic summer. So, permanent warming of the layer from the surface was balanced by permanent pumping of the colder air into the layer via general-circulation mechanisms. This balance yielded a quasi-stationary regime of turbulence that, in turn, assured accurate estimation of turbulent energies and fluxes, practically unachievable in the conditions of short-lived non-stationary convective layers typical of mid-latitudes. Turbulent energies and fluxes were calculated directly from the measured velocity and temperature fluctuations, whereas the pressure-velocity correlations happened to be negligibly small. Data on the viscous dissipation were retrieved via the Kolmogorov -5/3 power law ...